Vierter Gentechnologiebericht Bilanzierung einer Hochtechnologie - Hampel, Jürgen (Nomos Verlagsgesellschaft mbH & Co. KG, 2018)
The fourth Gene Technology Report by the interdisciplinary research group (IAG) of the same name at the Berlin-Brandenburg Academy of Sciences and Humanities (BBAW) takes stock of almost 20 years of work.